Iodine Catalyzed Microwave-Assisted Synthesis of 14-Aryl（Alkyl）-14H-dibenzo[a,j]xanthenes - 丁飞青 安礼涛 邹建平 (Chinese journal of chemistry, 2007)
A straightforward and effective procedure for the synthesis of 14-aryl（alkyl）-14H-dibenzo[aj]xanthenes was described using a catalytic amount of molecular iodine under microwave irradiation to afford the corresponding xanthenes in good yields.